Gambaran Organ Reproduksi Jantan dan Spermatozoa Kelinci New Zealand dan Kelinci Lokal - Eko Susetyarini; Poncojari Wahyono; Roimil Latifa; Endrik Nurrohman (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
This study aims to describe the reproductive organs and spermatozoa of local rabbits and New Zealand rabbits. This type of research is descriptive. The study was conducted at the Integrated Laboratory for maintenance and Biology Laboratory of the University of Muhammadiyah Malang for observing images of reproductive organs and spermatozoa. The study was conducted from April to June 2019. 3-month-old rabbits were obtained from farmers in the East Java city of Batu. The results showed that the overall weight of the reproductive organs of New Zealand male rabbits was 3.7 grams, the right testicular weight was 0.82 grams, the left testis was 0.78 grams, penile weight was 1.4 grams, 0.7 grams was heavy from the epididymic ducts and vases efferen. The length of the right testis is 1.2 cm, the length of the left testis is 1.1 cm, the penis length is 1.4 cm, the length of the right vas deferens is 6.8 cm, and the left vas deferens is 6.6 cm. In local rabbits the overall weight of the reproductive organs is 2.25 grams, the weight of the right testis is 0.51 grams, the left testis is 0.48 grams, the penis weight is 0.86 grams, 0.4 grams is the weight of the epididymic duct and the efferent vas. The length of the right testis is 0.6 cm, the left testis is 0.5 cm, the penis length is 1.2 cm, the length of the right vas deferens is 4.6 cm, the length of the left vas deferens is 4.4 cm. Spermatozoa cells are clearly visible in the head and tail, but the observation of the number of New Zealand spermatozoa cells is larger and relatively larger than the local rabbit spermatozoa.